Pectobacterium carotovorum Subsp. brasiliense Causing Soft Rot in Eggplant in Xinjiang, China - Wei He; Wenfang Luo; Junhui Zhou; Xiafen Zhu; Jianjun Xu (Microorganisms, 2023)
An outbreak of stem rot in eggplants was observed in Heshuo County, Xinjiang, during winter 2021–2022 in about 12–35% of the eggplants in the region (about 40 hm2). The infected tissues yielded a total of four bacterial strains, which were subsequently subjected to physiological and biochemical assays as well as molecular identification. Based on these analyses, the pathogen was identified as Pectobacterium carotovorum subsp. brasiliense. The pathogenicity was confirmed through the fulfillment of Koch’s postulates. The host range test confirmed the broad spectrum of species susceptible to infection by the strains. This study represents the first case of infection caused by P. carotovorum subsp. brasiliense resulting in stem rot in eggplant.